Characterization of physicochemical and microbial quality, functional properties, and shelf stability of fermented tigernut-based probiotic beverages - Yeboah, Stephen; Ohemeng, Agartha; Donkor, Leticia; Saalia, F. K.; Annor, George Amponsah; Kunadu, Angela Parry-Hanson (Frontiers in Food Science and Technology, 2023)
Tiger nuts and millet are indigenous underutilized crops in West Africa that have versatile applications in food processing. These crops are rich in fermentable carbohydrates, resistant starch, fiber, and micronutrients, making them ideal candidates for pre and probiotic (synbiotic) foods.This study utilized whole tiger nuts in dairy-millet-based fermented beverage called brukina, made it a synbiotic, and assessed the functional and physicochemical profile, microbial quality, and shelf stability of the beverage. The tiger nut-millet agglomerate was prepared by incorporating cellulosehydrolyzed tiger nut fibrous cake (TNF) and non-hydrolyzed TNF (10% and 15% respectively) into millet for 12-and 24-hours fermentation. Brukina produced from composite tiger nut milk: dairy in a ratio of 40%:60% was inoculated with the probiotic Lacticaseibacillus casei after pasteurization. The beverage was analyzed for physicochemical, proximate, functional properties and microbiological stability at 5°C and 25°C. The obtained data were subjected to analysis of variance (ANOVA) in Minitab version 17 using a general linear model to determine the variability, interactions, and significance of the measured product characteristics. The agglomerate Water Absorption Capacity (l/g) ranged from 0.70±0.17 to 0.89±0.17, Bulk Density (g/l) 0.55±0.04 to 0.63±0.00, and Swell Index (%) 1.62±0.08 to1.80±0.06. Agglomerate prepared from dough fermented for 12 hours had excellent functional characteristics and was selected for synbiotic brukina production. Moisture content of the product decreased (P<0.001) with tiger nut incorporation ranging from 78.85% to 70.45%, while sodium, phosphorus, protein, total carbohydrate, and crude fiber increased with tiger nut incorporation (P< 0.05). Synbiotic brukina supported the growth of L. casei attaining 11 log CFU/ml with a corresponding increase in lactic acid production and were microbiologically safe at 5°C and 25°C for 5 days as compared to unpasteurized and uninoculated probiotic control (P<0.05). The addition of whole tiger nuts and L. casei into brukina enhanced its nutritional content with a shelf stability of 3 days.